From the Social History of the Reformation (1960-1980) to the Reformation as Communication Process (1990-2000) - Gaganakis, Costas (Historein, 2013)
This article attempts to chart the “paradigm shift” from social history, dominant until the early 1980s, to new cultural history and the various interpretive trends it engendered in the 1990s and 2000s. The privileged field of investigation is the history of the Protestant Reformation, particularly in its urban aspect. The discussion starts with the publication of Bernd Moeller’s pivotal Reichsstadt und Reformation in the early 1960s – which paved the way for the triumphant invasion of social history in a field previously dominated by ecclesiastical or political historians, and profoundly imbued with doctrinal prerogatives – and culminates in the critical presentation of interpretive trends that appear to dominate in the 2010s, particularly the view and investigation of the Reformation as communication process.